Forma escolar, educação física e educação infantil : (im)pertinências - Rocha, Maria Celeste (2011)
The paper reflects about some issues that permeate the current debate about Children’s Education, aiming at understanding and discussing about its role/function, as well as discussing the insertion of the Physical Education in such educational segment. The work’s goal is to establish a critical dialogue with the Childhood Pedagogy; problematize the notion of school form as model for Children’s Education; identify how an insertion of the Physical Education teacher (specialist) is concretized in the view of the regent teachers, pedagogues and promoters; and, at last, verify how the Children’s Education Municipal Centers (CMEIs) organize the pedagogical work between the regent teachers and the specialist ones. It uses as reasons, the Hannah Arendt thought (1990), the proposal of a Pedagogy of Childhood (ROCHA, 1998) and also the Theory of the School Form (GUY VINCENT; LAHIRE; THIN, 2001). It intertwines the theoretical referential with the collect data through the semi structured interviews with the regent teachers of the classrooms, specialists in Physical Education (promoters) and pedagogues working in Children’s Education institutions in the district of Vitória, State of Espírito Santo. It shows a tension that is present in the educative process of the little children. Regarding Children’s Education, both the discipline students and the teachers working in their institutions have as fundamental assumption that the function of Children’s Education is tied to the dimension of taking care and educating in an inseparable way. Although some teachers, in their speeches, take such assumption into consideration, what stood out was the concern about preparing the child for the Elementary Teaching. Regarding the Physical Education insertion in the Children’s Education, the study highlights that that theme is presented even more controversial, because, besides divided opinions between defense and denial of that insertion, it is not very clear which is the specificity of that curricular component for Children’s Education, in the academic environment and also in the proposals concerning education for the little children. Without the intention of defending or denying the presence of Physical Education in the Children’s Education, the study raises issues that need to be considered prior the elaboration of any proposal of Physical Education specificity for that education modality.